Could the use of saliva substitutes improve food oral processing in individuals with xerostomia? A systematic review. Issue 3 (1st March 2021) - Piaton, Sophie; Duconseille, Anne; Roger‐Leroi, Valérie; Hennequin, Martine
Abstract: Xersotomia is associated with food avoidance and low nutritional assessment. This review seeks to document whether products called "saliva substitutes" or "artificial saliva" can really replace saliva in food oral processing. Pubmed and Science Direct were searched for articles using the keywords "saliva substitutes" and "artificial saliva." An advanced search was applied using the terms "xerostomia" and/or "food oral processing" and/or "eating" and/or "mastication" and/or "chewing" and/or "swallowing." The analysis methods and the inclusion criteria were documented in a protocol published in the International prospective register of systematic reviews (PROSPERO with the registration number CRD42019124585). The search included 43 articles, published between 1979 and 2017. Among the included studies, 17 were observational studies, 5 were pilot studies, 21 were crossover studies, and 14 of these studies were blinded. The Strobe score for the included articles varied from 7.5 to 20. The possible effects of the use of saliva substitutes on the ingestion function were poorly investigated. No evidence was based on physiological studies. It is unknown whether using a saliva substitute has an effect on the composition and rheological properties of the food bolus, on the lubrication of the oral and laryngeal mucosa or on both phenomena. Moreover, saliva substitutes were not formulated to improve food oral processing and most of them are flavored. New saliva substitutes and artificial saliva should be designed and formulated to improve food oral processing.